2010
DOI: 10.1021/pr1005108
|View full text |Cite
|
Sign up to set email alerts
|

A Proteome-Scale Identification of Novel Antigenic Proteins inMycobacterium tuberculosistoward Diagnostic and Vaccine Development

Abstract: Tuberculosis (TB) remains to be a major infectious disease throughout the world. However, the current vaccine for TB has variable protective efficacy, and there is no commercially available serodiagnostic test for this disease with acceptable sensitivity and specificity for routine laboratory use. One of the potential strategies in developing a new diagnostic method and in improving the TB vaccine involves the identification of novel antigenic candidates. This paper aims to identify systematically the novel an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 97 publications
2
29
0
Order By: Relevance
“…S4). According to the results of first-round screening, these two studies found that 29 out of 249 and 484 proteins were positive as determined by ELISA assay and protein array, respectively (26,27). Other antigenic proteins were also identified in our study (31 proteins were identified in addition to those reported by Li et al (26), and another 55 proteins in addition to those reported by Kunnath-Velayudhan et al (27)).…”
Section: Proteinsupporting
confidence: 80%
See 2 more Smart Citations
“…S4). According to the results of first-round screening, these two studies found that 29 out of 249 and 484 proteins were positive as determined by ELISA assay and protein array, respectively (26,27). Other antigenic proteins were also identified in our study (31 proteins were identified in addition to those reported by Li et al (26), and another 55 proteins in addition to those reported by Kunnath-Velayudhan et al (27)).…”
Section: Proteinsupporting
confidence: 80%
“…A commercially used recombinant 38-kDa protein has been reported to have a specificity of 94% in smear-positive TB patients, supporting the use of tests for serological reactivity (37). In previous studies, two methods, protein array and ELISA, have been used to detect antibody responses when screening for M. tuberculosis antigens (26,27). In our study, 1,250 M. tuberculosis proteins were screened for antibody response using a semi-quantitative Western blot assay.…”
Section: Proteinmentioning
confidence: 63%
See 1 more Smart Citation
“…Effective cellular and humoral immune responses depend on targeting accessible molecules, which tend to be on the surface of a pathogen (87). With respect to mycobacteria, putative and known surface-exposed proteins comprise a substantial proportion of antigens observed in comprehensive screens using sera from mycobacterium-infected hosts (37,42,45,85). The characterization of these proteins improves our understanding of bacterial pathogenesis and host immunity, providing insights that can lead to new diagnostic tools and vaccines (38,87).…”
mentioning
confidence: 99%
“…These antigens might offer new targets for vaccine development. Nearly, an immunoproteome microarray study of M. tuberculosis-proteins with sera from patients was developed [34], in which, 3 novel antigens, namely, Rv1987, Rv3807c, and Rv3887c, provided better sensitivity and accuracy for TB detection.…”
Section: Proteins For Drug Developmentmentioning
confidence: 99%